2014
DOI: 10.1080/02673037.2014.933782
|View full text |Cite
|
Sign up to set email alerts
|

Housing Trajectories Across the Urban Hierarchy: Analysis of the Longitudinal Survey of Immigrants to Canada, 2001–2005

Abstract: Within the Canadian housing market, some immigrants move quickly to quality, affordable housing, whereas others struggle through both systematic and institutional barriers. This article uses Statistics Canada's Longitudinal Survey of Immigrants to Canada (LSIC) -capturing the settlement and integration experiences of immigrants from 2001 to 2005-and investigates housing conditions (housing satisfaction, rates of homeownership, crowding, and affordability) over three survey waves across the Canadian urban hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Immigrants' geographical location was found to be an important factor influencing labour market integration (Buzdugan and Halli 2009) and incidence of poverty (Picot et al 2008). This finding which indicates that newcomers who reside in the most popular immigrant destinations-Montreal, Vancouver and Toronto-were less likely to own homes relative to other immigrants in other CMAs may be due to the expensive housing markets in these areas; making it difficult for immigrants to attain homeownership (Simone and Newbold 2014).…”
Section: Multivariate Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Immigrants' geographical location was found to be an important factor influencing labour market integration (Buzdugan and Halli 2009) and incidence of poverty (Picot et al 2008). This finding which indicates that newcomers who reside in the most popular immigrant destinations-Montreal, Vancouver and Toronto-were less likely to own homes relative to other immigrants in other CMAs may be due to the expensive housing markets in these areas; making it difficult for immigrants to attain homeownership (Simone and Newbold 2014).…”
Section: Multivariate Resultsmentioning
confidence: 95%
“…Therefore, the reduction in social housing stock over the decades has pushed low income earners including refugees and immigrants into the housing markets where prices are determined by market forces (Skaburskis and Mok 2000;Bunting et al 2004;Murdie 2008). A recent study by Simone and Newbold (2014), suggests that overpriced housing markets in the most popular immigrant destinations in Canada (Montreal, Vancouver and Toronto) makes homeownership difficult. In earlier research, Moore and Skaburskis (2004) found that housing affordability determined by income levels is identified as critical in influencing the geographical locations low income groups such as immigrants can opt to live.…”
Section: Understanding Immigrant Housing Trajectoriesmentioning
confidence: 95%
See 1 more Smart Citation
“…Immigrants' performance of belonging in and around the GTA's networked enclaves was largely influenced by their housing trajectory. Home ownership is a desired outcome for the vast majority of newcomers in Canada (Simone & Newbold, 2014) and is an important marker of spatial and temporal permanence and belonging (Lung-Amam, 2017). In this study, property ownership of singledetached homes was necessary to support the multigenerational living preferred by many participants, and the affordability of housing in the suburbs was a major draw to Peel Region.…”
Section: Considering Housing Trajectories and Settlement Experiences In The Suburbsmentioning
confidence: 99%
“…We used longitudinal empirical data that spanned the eight months following a refugee's grant of asylum and binary logistic regression to assess the relative importance of factors associated with refugee homelessness that have been identified in the existing literature. Although longitudinal surveys of refugee homelessness have been conducted in Australia (Flatau et al, 2015) and Canada (Hiebert, 2009;Mendez et al, 2006;Simone & Newbold, 2014), such analysis has not previously been carried out for England. Our analysis underlines the centrality of immigration policy to the production of refugee homelessness, while also demonstrating the impact of certain broader life experiences and demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%